2019
DOI: 10.7861/futurehosp.6-1-s1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Ambulatory Care Unit (ACU) on ‘true admission avoidance’ at Basingstoke and North Hampshire Hospital

Abstract: The Ambulatory Care Unit (ACU) is a recent addition to Basingstoke and North Hampshire Hospital. In January 2017, additional acute medical consultants were appointed to help develop the service. The clinic is consultant led and operates Monday-Friday from 09.00-18.00. ACU accepts referrals directly from GPs and operates a push/pull system for the Emergency Department (ED). Out-of-hours referrals can be made via the medical registrar on call. Before expanding the service further, we studied the true impact of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…While results were mixed, Coffey et al 10 concluded that ambulatory care interventions ‘generally had a positive effect on most outcomes’. In addition, evaluations of two ambulatory care services in the United Kingdom, a GP‐referred unit 19 and a same‐day ambulatory emergency care service 20 reported reductions in 30‐day readmission rates and mortality. These programmes are similar to MACS in providing rapid service in subacute setting for GP‐referred and clinician‐referred patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While results were mixed, Coffey et al 10 concluded that ambulatory care interventions ‘generally had a positive effect on most outcomes’. In addition, evaluations of two ambulatory care services in the United Kingdom, a GP‐referred unit 19 and a same‐day ambulatory emergency care service 20 reported reductions in 30‐day readmission rates and mortality. These programmes are similar to MACS in providing rapid service in subacute setting for GP‐referred and clinician‐referred patients.…”
Section: Discussionmentioning
confidence: 99%
“…GP GP-referred unit 19 and a same-day ambulatory emergency care service 20 reported reductions in 30-day readmission rates and mortality. These programmes are similar to MACS in providing rapid service in subacute setting for GP-referred and clinician-referred patients.…”
Section: Ward-referredmentioning
confidence: 99%
See 2 more Smart Citations